Porous ceramic membrane crystallization device and method based on photo-thermal enhancement
By forming a carbon layer on the surface of the porous ceramic membrane and using photothermal heating, combined with the negative pressure module, the problem of temperature polarization of the porous ceramic membrane during the membrane crystallization process is solved, and continuous film crystallization and energy consumption reduction under low temperature conditions are achieved .
Patent Information
- Application Number
- CN202411574001.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-10
AI Technical Summary
The existing porous ceramic membranes are prone to temperature polarization during membrane crystallization, resulting in increased energy consumption and decreased crystallization driving force, and the membrane crystallization cannot be continuously carried out.
Design a porous ceramic membrane crystallization device based on photothermal enhancement. By forming a carbon layer on the surface of the hollow porous ceramic membrane module, and forming the carbon layer by using vapor deposition method to improve the light heating efficiency, combined with a negative pressure module to control the temperature, avoiding Temperature polarization.
Continuous membrane crystallization under low temperature conditions (20-40℃), reducing energy consumption, avoiding the occurrence of temperature polarization, and improving the purity and yield of crystallization.
Smart Images

Figure CN119280875A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of resource recovery and utilization, and more specifically, to a porous ceramic membrane crystallization device and method based on photothermal enhancement. Background Art
[0002] With the rapid development of modern science and technology industries, people's demand for metals and minerals is increasing day by day. At present, the supply of metals and minerals is mainly met by mining minerals, and this limited resource is being depleted at an increasingly rapid rate. In addition, the difficulty and cost of mining the remaining minerals are increasing, and it has also caused pollution problems such as air, water, and soil. Therefore, it is necessary to seek new sources of metals and minerals. Studies have shown that a large amount of metals and minerals exist in the form of dissolved substances in seawater, brine, and wastewater generated by various production processes. The recovery of metals and minerals from these liquid resources is called "water mining", which not only helps to strengthen the sustainable supply of resources, but also can transform "waste" into products, which has significant economic and environmental value. Therefore, the development of technology to recover metals and minerals from liquids is crucial to the sustainable supply of metals and minerals.
[0003] Crystallization is an important means of recovering metals and minerals from liquids. Commonly used crystallization methods include evaporation, cooling, antisolvent and membrane crystallization. When the solute solubility is less affected by temperature, the evaporation method can be used for crystallization. Its essence is to concentrate the solute to a sufficient supersaturation by evaporating the liquid solvent, thereby promoting the solute to crystallize into a solid phase. Obviously, evaporation crystallization requires a lot of heat and it is difficult to control the crystal size. When the solute solubility is sensitive to temperature, the cooling method can be used for crystallization. The principle is to reach a supersaturated state by lowering the solution temperature. This process can better control the crystal growth dynamics, but the applicable products are limited, the energy consumption is high, the equipment cost is high, and the crystallizer is easy to corrode. The antisolvent method is to use an antisolvent to dilute the saturated solution to significantly reduce the solute solubility. This process can finely control the crystal quality (crystal structure, size, shape), but the cost of the antisolvent is high, and the solvent / antisolvent mixture needs to be treated, otherwise it will cause environmental pollution.
[0004] In recent years, with the rapid development of membrane materials, membrane crystallization technology has received more and more attention and research. Compared with traditional crystallization technology, membrane crystallization can provide a large nucleation interface (i.e., the membrane itself), thereby realizing heterogeneous nucleation, which can not only effectively control the crystal size, but also reduce the supersaturation required for crystallization by providing nucleation sites, and finally obtain crystals with high purity, narrow grain distribution, and adjustable polycrystalline structure.
[0005] Membrane crystallization generally uses polymer membranes, which have good selectivity and permeability and low cost, but also have some problems, such as poor thermal and chemical stability, easy pollution and scaling, etc. Compared with polymer membranes, porous ceramic membranes have the advantages of high mechanical strength, heat resistance, corrosion resistance, strong anti-pollution ability, and easy cleaning. At present, the research on the use of porous ceramic membranes for membrane crystallization is still rare.
[0006] The document "Incorporation of composite metal-PVP derived carbon membranes for the percrystallisation of salt water" applies a mixed solution of PVP and metal salts on a porous ceramic membrane, and then forms a carbon membrane by pyrolysis. The introduction of metal salts is mainly used to adjust the microstructure of the carbon membrane. The special microstructure of the carbon membrane can improve the flux during crystallization. However, the driving force of the crystallization process in this document mainly comes from the heating of the feed liquid, which is not only energy-intensive; but also once the temperature of the feed liquid is high, it is easy to cause temperature polarization on the porous ceramic membrane substrate, that is, the temperature of the porous ceramic membrane is lower than the temperature of the feed liquid; temperature polarization will lead to further increase in energy consumption and decrease in driving force. In severe cases, it will also cause the porous ceramic membrane to be flooded, and the membrane crystallization cannot continue. Summary of the invention
[0007] The primary purpose of the present invention is to overcome the problem that the membrane crystallization technology of the above-mentioned existing porous ceramic membranes is still less studied, or the porous ceramic membranes are prone to temperature polarization and cannot continue to crystallize the membrane, and to provide a porous ceramic membrane crystallization device based on photothermal enhancement.
[0008] A further object of the present invention is to provide a method for recovering salt from a salt solution.
[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0010] A porous ceramic membrane crystallization device based on photothermal enhancement, the porous ceramic membrane crystallization device comprising a box, an evaporation crystallization module arranged in the box, and a negative pressure module for forming a negative pressure inside the box;
[0011] The evaporation crystallization module includes a hollow porous ceramic membrane component and a carbon layer formed on the outer surface of the hollow porous ceramic membrane component by a vapor deposition method;
[0012] The box body is provided with a light-transmitting portion or a light-emitting component so that the evaporation and crystallization module is illuminated by light.
[0013] In order to overcome the problem of temperature polarization that porous ceramic membranes are prone to during the membrane crystallization process, the inventors of the present invention have attempted to design illumination and negative pressure in the porous ceramic membrane crystallization device to coordinate the membrane crystallization process; wherein illumination is mainly used to heat the hollow porous ceramic membrane assembly. However, it is difficult to significantly increase the temperature of the hollow porous ceramic membrane assembly by irradiating the hollow porous ceramic membrane assembly with light, so the problem of temperature polarization cannot be solved.
[0014] The inventors of the present invention continued to study and found that a carbon layer is formed on the outer surface of the hollow porous ceramic membrane assembly by vapor deposition. The carbon layer will not only significantly increase the temperature of the evaporation crystallization module due to the vibration of electrons caused by light irradiation, but also because the carbon layer is formed by vapor deposition, it has good adhesion with the hollow porous ceramic membrane assembly during the process of light heating to a higher temperature, so the carbon layer is not easy to fall off. This allows the porous ceramic membrane crystallization device of the present invention to perform continuous membrane crystallization on a relatively low temperature (such as 20-40°C) feed liquid and avoid the occurrence of temperature polarization, thereby avoiding further increase in energy consumption and a decrease in the driving force for crystallization due to temperature polarization.
[0015] If other methods are used to form the carbon layer (for example, applying an organic solution and then pyrolyzing it), once the hollow porous ceramic membrane assembly is heated to a higher temperature by light irradiation, the carbon layer will easily fall off the surface of the hollow porous ceramic membrane assembly, and continuous crystallization will not be possible.
[0016] In addition, compared with the method of heating the feed liquid to a higher temperature to perform membrane crystallization, the porous ceramic membrane crystallization device of the present invention uses light to heat the evaporation crystallization module, and the temperature of the feed liquid does not need to be very high, so the energy consumption can be significantly reduced.
[0017] Preferably, the box body is provided with a salt solution inlet and a salt solution outlet, and the salt solution inlet and the salt solution outlet are respectively connected to two ends of the hollow porous ceramic membrane assembly.
[0018] Preferably, the hollow porous ceramic membrane assembly is a plurality of hollow porous ceramic membrane tubes, or a hollow porous ceramic membrane plate having a plurality of channels for passing a salt solution.
[0019] More preferably, the number of the plurality of hollow porous ceramic membrane tubes is 4 to 8, and the inner diameter of each hollow porous ceramic membrane tube is 6 to 10 mm.
[0020] More preferably, the hollow porous ceramic membrane plate comprises 10 to 30 parallel channels, and the cross-sectional area of each channel is 25 to 100 mm 2 .
[0021] Preferably, the porous ceramic membrane of the hollow porous ceramic membrane assembly has a thickness of 2 to 4 mm.
[0022] Preferably, the pore size distribution of the porous ceramic membrane of the hollow porous ceramic membrane assembly is 100 to 300 nm.
[0023] Preferably, the process of the vapor deposition method is: placing the hollow porous ceramic membrane assembly in a mixed gas flow of ethylene and hydrogen at 700 to 900° C. and reacting for 10 to 20 minutes.
[0024] Ethylene can be pyrolyzed into carbon at a certain temperature and firmly attached to the surface of the hollow porous ceramic membrane assembly to form a carbon layer. The mixed gas flow contains hydrogen, which can adjust the uniformity of the carbon layer on the surface of the hollow porous ceramic membrane assembly on the one hand, and on the other hand, it can adjust the pore structure of the membrane, which is more conducive to the penetration of the feed liquid during the membrane crystallization process.
[0025] More preferably, in the mixed gas flow, the flow rate of ethylene is 30 to 50 mL / min, and the flow rate ratio of ethylene to hydrogen is (30 to 50): (15 to 25).
[0026] Preferably, the hollow porous ceramic membrane assembly further comprises metal nanoparticles supported on the carbon layer.
[0027] Loading metal nanoparticles on the carbon layer is beneficial to further increase the temperature of the hollow porous ceramic membrane assembly after being irradiated by light, thereby further reducing energy consumption and improving the yield and purity of crystallization.
[0028] More preferably, the process of loading the metal nanoparticles on the carbon layer is as follows: disperse the metal powder in water, crush and ultrasonicate to obtain a suspension; immerse the hollow porous ceramic membrane assembly with a carbon layer formed on the outer surface in the suspension for 1 to 5 minutes, then extract it at a speed of 5 to 15 cm / min, vacuum filter it, and dry it.
[0029] More preferably, the usage ratio of the metal powder to water is 1-5 g:15 mL.
[0030] Further preferably, the crushing and ultrasonication process is: using a cell crusher to ultrasonicate for 3 to 8 minutes.
[0031] More preferably, the process of loading the metal nanoparticles on the carbon layer is performed 3 to 5 times.
[0032] Further preferably, the particle size of the metal powder is nanometer scale.
[0033] More preferably, the metal nanoparticles are at least one of nickel, gold or silver.
[0034] Preferably, the carbon layer has a thickness of 5 to 10 μm.
[0035] Preferably, the box is a glass box.
[0036] Preferably, the negative pressure module is a vacuum pump.
[0037] Preferably, the light irradiated is sunlight or simulated sunlight.
[0038] A method for recovering salt from a salt solution, using the porous ceramic membrane crystallization device to treat the salt solution, comprises the following steps:
[0039] Starting the negative pressure module forms a negative pressure inside the box of the porous ceramic membrane crystallization device, and then the salt solution flows through the hollow porous ceramic membrane assembly of the evaporation crystallization module and penetrates into the outer surface of the evaporation crystallization module, evaporating and crystallizing, thereby realizing salt recovery.
[0040] Preferably, the temperature of the salt solution is 20-40° C.; the concentration of the salt solution is 15-25 wt %; and the negative pressure is 0.3-1.3 kPa.
[0041] Preferably, the flow rate of the saline solution is 80-200 ml / min.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The porous ceramic membrane crystallization device of the present invention can continuously perform membrane crystallization on a relatively low temperature (eg, 20-40° C.) feed solution and avoid the occurrence of temperature polarization, thereby avoiding further increase in energy consumption and decrease in driving force for crystallization due to temperature polarization.
[0044] In addition, compared with the method of heating the feed liquid to a higher temperature to perform membrane crystallization, the porous ceramic membrane crystallization device of the present invention uses light to heat the evaporation crystallization module, and the temperature of the feed liquid does not need to be very high, so the energy consumption can be significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a schematic diagram of the structure of the porous ceramic membrane crystallization device of Example 1.
[0046] Figure 2 This is a schematic diagram of the structure of the porous ceramic membrane crystallization device of Example 3.
[0047] Figure 3 This is a graph showing the temperature changes of the untreated (not loaded with carbon layer and nickel nanoparticles) hollow porous ceramic membrane tube (denoted as hollow porous ceramic membrane tube A) of Example 1 and the hollow porous ceramic membrane tube loaded with carbon layer and nickel nanoparticles after being irradiated with light. DETAILED DESCRIPTION
[0048] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0049] Example 1
[0050] This embodiment provides a porous ceramic membrane crystallization device based on photothermal enhancement, such as Figure 1 As shown, the porous ceramic membrane crystallization device comprises a box body 1, an evaporation crystallization module 2 mounted in the box body 1, and a negative pressure module 3 for forming a negative pressure inside the box body 1; the negative pressure module 3 is a vacuum pump;
[0051] The evaporation crystallization module 2 includes a hollow porous ceramic membrane assembly, a carbon layer on the outer surface of the hollow porous ceramic membrane, and nickel nanoparticles loaded on the carbon layer; the box is a glass box. The hollow porous ceramic membrane assembly includes 5 hollow porous ceramic membrane tubes, each of which has an inner diameter of 8 mm; the thickness of the porous ceramic membrane of the hollow porous ceramic membrane tube is 2 mm, and the pore size is 200 nm;
[0052] The box 1 is provided with a solution inlet 4 and a solution outlet 5, which are respectively connected to the two ends of each hollow porous ceramic membrane tube. The top surface of the box 1 is inclined so that the hollow porous ceramic membrane assembly can be exposed to solar radiation with the largest possible area.
[0053] The preparation method of the hollow porous ceramic membrane assembly is as follows:
[0054] 1) First, the hollow porous ceramic membrane tube is placed in the constant temperature zone of the quartz tube of the tubular furnace, and the temperature is raised to 700°C at a rate of 10°C / min in an N2 atmosphere, and then maintained at 700°C, C2H4 and H2 are introduced into the quartz tube at flow rates of 30mL / min and 15mL / min, respectively, and the reaction time is set to 10min. Then, H2 is removed, and then C2H4 is removed, and the temperature is cooled to room temperature in an N2 atmosphere to obtain a hollow porous ceramic membrane tube loaded with a carbon layer;
[0055] 2) First weigh 5 grams of nickel powder (nanoscale) and add it to 75 mL of deionized water. Ultrasonicate the cell crusher for 5 minutes to form a uniform suspension. Then, perform the soaking-filtration-drying treatment: first seal the two ends of the hollow porous ceramic membrane tube loaded with carbon layer with hot melt adhesive, vertically soak it in the suspension for 2 minutes, and extract it at a speed of ~5 cm / min. Then, place the hollow porous ceramic membrane tube loaded with carbon layer soaked in the suspension in a vacuum environment for filtration, so that the nickel nanoparticles are firmly adsorbed on the carbon layer, and then place it in an oven at 60°C and take it out after 6 hours. Repeat the above soaking-filtration-drying treatment operation 3 times to obtain a hollow porous ceramic membrane assembly.
[0056] Example 2
[0057] The present embodiment provides a porous ceramic membrane crystallization device based on photothermal enhancement, which is basically the same as Example 1, except that: in the first step of the preparation method of the hollow porous ceramic membrane assembly, the flow rates of C2H4 and H2 are 50 mL / min and 25 mL / min, respectively; in the second step, 25 grams of nickel powder is weighed and added to 75 mL of deionized water; in the second step, it is extracted at a speed of ~15 cm / min.
[0058] Example 3
[0059] This embodiment provides a porous ceramic membrane crystallization device based on photothermal enhancement, which is basically the same as embodiment 1, except that: Figure 2 As shown, the hollow porous ceramic membrane assembly is a hollow porous ceramic membrane plate, which includes 17 parallel channels, and the cross-sectional area of each channel is 25mm 2 The solution inlet 4 and the solution outlet 5 are respectively connected to the two ends of each channel.
[0060] The preparation method of the hollow porous ceramic membrane assembly is as follows:
[0061] 1) First, the hollow porous ceramic membrane plate is placed in the constant temperature zone of the quartz tube of the tubular furnace, and the temperature is raised to 700°C at a rate of 10°C / min in an N2 atmosphere, and then maintained at 700°C, C2H4 and H2 are introduced into the quartz tube at flow rates of 30mL / min and 15mL / min, respectively, and the reaction time is set to 10min, and then H2 is removed, and then C2H4 is removed, and the temperature is cooled to room temperature in an N2 atmosphere to obtain a hollow porous ceramic membrane plate loaded with a carbon layer;
[0062] 2) First weigh 5 grams of nickel powder and add it to 75 mL of deionized water. Ultrasonicate the cell crusher for 5 minutes to form a uniform suspension. Then, soak-filter-dry: first seal the two ends of the channel of the hollow porous ceramic membrane plate loaded with carbon layer with hot melt adhesive, vertically soak it in the suspension for 2 minutes, and extract it at a speed of ~5 cm / min. Then, place the hollow porous ceramic membrane plate loaded with carbon layer soaked in the suspension in a vacuum environment, and use vacuum filtration to load nickel nanoparticles on the carbon layer. Then put it in an oven at 60°C and take it out after 6 hours. Repeat the above soaking-filtration-drying operation 3 times to obtain a hollow porous ceramic membrane assembly.
[0063] Example 4
[0064] The present embodiment provides a porous ceramic membrane crystallization device based on photothermal enhancement, which is different from Example 1 in that the hollow porous ceramic membrane component is a hollow porous ceramic membrane tube loaded with a carbon layer but not loaded with nickel nanoparticles, that is, the hollow porous ceramic membrane tube loaded with a carbon layer obtained in step 1) of the preparation method of the hollow porous ceramic membrane component of Example 1.
[0065] Comparative Example 1
[0066] This comparative example provides a porous ceramic membrane crystallization device, which is different from Example 1 in that the hollow porous ceramic membrane component is an untreated (not loaded with a carbon layer and nickel nanoparticles) hollow porous ceramic membrane tube.
[0067] Performance Testing
[0068] 1. Temperature characterization after illumination
[0069] The untreated (not loaded with carbon layer and nickel nanoparticles) hollow porous ceramic membrane tube (referred to as hollow porous ceramic membrane tube A) and the hollow porous ceramic membrane tube loaded with carbon layer and nickel nanoparticles (referred to as hollow porous ceramic membrane tube B) of Example 1 were taken, and the changes in the surface temperatures of the two were recorded by an infrared thermal camera under the irradiation of a xenon lamp. The results are as follows: Figure 1 As shown. Figure 3 It can be seen that in the initial stage, the surface temperature of the hollow porous ceramic membrane tube A and the hollow porous ceramic membrane tube B is between 26℃ and 30℃, and at 800W / m 2After 600s of illumination with simulated sunlight intensity, the surface temperature of hollow porous ceramic membrane tube A was about 35.8°C, while the surface temperature of hollow porous ceramic membrane tube B rose rapidly and finally reached about 71°C. This is because: when light shines on the surface of hollow porous ceramic membrane tube B, it may trigger the electron transition from the low-energy orbit to the high-energy orbit inside the molecule, and these excited electrons reach a relaxed state through the interaction between electrons and phonons. Therefore, the absorbed light energy is transferred from these excited electrons to the vibration of the entire crystal structure. When the incident light shines on the surface of hollow porous ceramic membrane tube B, it can excite the electrons in the molecule to transition from low-energy orbits to high-energy orbits. These excited electrons then relax by interacting with phonons, transferring the absorbed light energy to the vibration of the entire crystal structure. In addition, when the vibration frequency of the incident light matches the resonant frequency of the free electrons on the surface of nickel nanoparticles, it triggers the collective excitation of electrons to produce coherent oscillations. These excited hot electrons resonate with the incident electromagnetic field, causing the free electron gas inside the particles to oscillate and generate heat energy, thereby significantly increasing the surface temperature of the hollow porous ceramic membrane tube B. This experimental phenomenon shows that the evaporation crystallization module of the porous ceramic membrane crystallization device based on photothermal enhancement of the present invention can reach a temperature significantly higher than that of the room temperature solution (20-40°C) under illumination conditions, which makes it possible to avoid the occurrence of temperature polarization.
[0070] 2. Film crystallization performance test
[0071] Based on the porous ceramic membrane crystallization device of Examples 1 to 4 and Comparative Example 1, a process for recovering sodium chloride from a sodium chloride solution is performed, comprising the following steps:
[0072] Start the vacuum pump to form a negative pressure (1000Pa) inside the box of the porous ceramic membrane crystallization device, and then the sodium chloride solution (25wt%, 100ml / min, 40°C) enters the hollow porous ceramic membrane assembly from the solution inlet and flows out through the solution inlet. In the process of flowing through the hollow interior of the hollow porous ceramic membrane assembly, the sodium chloride solution penetrates into the surface of the evaporation crystallization module to form a thin film, which evaporates rapidly under the dual effects of light, heat and water vapor pressure difference. After the crystals grow to a critical size on the outer surface of the evaporation crystallization module, they fall off into the glass box, thereby realizing the simultaneous recovery of crystals and water.
[0073] After running for a period of time, the energy consumption, sodium chloride production capacity and sodium chloride purity of the device of each embodiment and comparative example were recorded. The results are shown in Table 1.
[0074] Table 1
[0075]
[0076] From Table 1, we can see that:
[0077] When the porous ceramic membrane crystallization device based on photothermal enhancement of Examples 1 to 4 performs membrane crystallization, the energy consumption is all below 512 kJ / kg, and the yield is all at 4.1 kg / (m 2 h) and above, the purity is above 97%, indicating that the porous ceramic membrane crystallization device based on photothermal enhancement of the present invention has low energy consumption for membrane crystallization and high production capacity and purity of sodium chloride.
[0078] The porous ceramic membrane crystallization device of Comparative Example 1 was not loaded with a carbon membrane, and the hollow porous ceramic membrane tube was quickly flooded after operation, making it impossible to continue membrane crystallization.
[0079] In addition, the temperature of the hollow porous ceramic membrane assembly of the porous ceramic membrane crystallization device during the crystallization process was measured, and the temperatures of the hollow porous ceramic membrane assemblies of Examples 1 to 4 were respectively maintained above 43.2°C, 45.8°C, 48.5°C and 41.7°C, which indicates that the temperature of the hollow porous ceramic membrane assembly of the porous ceramic membrane crystallization device is always higher than the temperature of the sodium chloride solution (40°C), further indicating that the porous ceramic membrane crystallization device of the present invention can avoid the occurrence of temperature polarization during membrane crystallization.
[0080] The hollow porous ceramic membrane tubes of the hollow porous ceramic membrane assembly of the porous ceramic membrane crystallization device of Comparative Example 1 were not subjected to property modification treatment, and were flooded soon after operation, making it impossible to continue membrane crystallization.
[0081] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A porous ceramic membrane crystallization device based on photothermal enhancement, characterized in that: The porous ceramic membrane crystallization device comprises a housing (1), an evaporation crystallization module (2) arranged in the housing (1), and a negative pressure module (3) for forming a negative pressure inside the housing (1); The evaporation crystallization module (2) comprises a hollow porous ceramic membrane component and a carbon layer formed on the outer surface of the hollow porous ceramic membrane component by a vapor deposition method; The box body (1) is provided with a light-transmitting portion or a light-emitting component so that the evaporation and crystallization module (2) is illuminated by light.
2. The porous ceramic membrane crystallization device according to claim 1, characterized in that: The box body (1) is provided with a salt solution inlet (4) and a salt solution outlet (5), and the salt solution inlet (4) and the salt solution outlet (5) are respectively connected to two ends of the hollow porous ceramic membrane assembly.
3. The porous ceramic membrane crystallization device according to claim 1, characterized in that: The hollow porous ceramic membrane components are a plurality of hollow porous ceramic membrane tubes, or a hollow porous ceramic membrane plate having a plurality of channels for passing a salt solution.
4. The porous ceramic membrane crystallization device according to claim 1, characterized in that: The membrane thickness of the hollow porous ceramic membrane assembly is 2 to 4 mm.
5. The porous ceramic membrane crystallization device according to claim 1, characterized in that: The pore size distribution of the porous ceramic membrane of the hollow porous ceramic membrane assembly is 100-300 nm.
6. The porous ceramic membrane crystallization device according to claim 1, characterized in that: The process of the vapor deposition method is: placing the hollow porous ceramic membrane assembly in a mixed gas flow of ethylene and hydrogen at 700-900° C. and reacting for 10-20 minutes.
7. The porous ceramic membrane crystallization device according to claim 1, characterized in that: The hollow porous ceramic membrane assembly further includes metal nanoparticles supported on the carbon layer.
8. The porous ceramic membrane crystallization device according to claim 1, characterized in that: The thickness of the carbon layer is 5-10 μm.
9. A method for recovering salt from a salt solution, characterized in that: The method of treating a salt solution by using the porous ceramic membrane crystallization device according to any one of claims 1 to 8 comprises the following steps: The negative pressure module is started to form a negative pressure inside the housing (1) of the porous ceramic membrane crystallization device, and then the salt solution flows through the hollow porous ceramic membrane assembly of the evaporation crystallization module (2) and penetrates into the outer surface of the evaporation crystallization module (2), evaporating and crystallizing, thereby realizing salt recovery.
10. The method according to claim 9, characterized in that: The temperature of the salt solution is 20-40° C.; the concentration of the salt solution is 15-25 wt %; and the negative pressure is 0.3-1.3 kPa.